2012
DOI: 10.1682/jrrd.2011.04.0067
|View full text |Cite
|
Sign up to set email alerts
|

Energy consumption during prosthetic walking and physical fitness in older hip disarticulation amputees

Abstract: Abstract-The objective of this study is to investigate energy consumption during prosthetic walking and physical fitness in older hip disarticulation (HD) subjects and to examine the ambulatory outcome in a community setting. The subjects were seven unilateral HD amputees with an average age of 67.7 +/-3.9 yr. Energy consumption was measured during prosthetic walking at each individual's comfortable walking speed (CWS) by means of a portable telemetric system. An incremental exercise test was performed to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Meta-analysis was not possible, as the studies of like outcome measures did not observe the same homogeneous patient characteristics; mainly, level, etiology, and mean ages were heterogeneous among these studies (1014). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meta-analysis was not possible, as the studies of like outcome measures did not observe the same homogeneous patient characteristics; mainly, level, etiology, and mean ages were heterogeneous among these studies (1014). …”
Section: Resultsmentioning
confidence: 99%
“…Linberg et al., in a high quality article, reported a significant difference in 6MWT performance between bilateral TTA patients and TFA patients, with bilateral TTA patients walking further (12). Chin et al reported, in a medium quality study, solely on the hip disarticulation amputee (HDA), where older HDA patients in good physical condition and with a low prevalence of comorbidities were able to successfully walk with a prosthesis in a community setting (10). Czerniecki et al reported the rates of success were similar: 35%, 31%, and 33% of amputees with transmetatarsal (TM), TTA, and TFA, respectively, achieved mobility success when seen in a comprehensive inpatient rehabilitation unit (27).…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Those who survive are often disfigured, institutionalized, and dependent on others for mobility. [6][7][8] For these reasons, alternative methods to treat nonhealing proximal limb stumps in this population of patients are very attractive. 9 HBOT is an adjunctive treatment that increases oxygen tension, improves cellular metabolism in ischemic tissues, and inhibits inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Those with hip disarticulation miss their abilities to stand and walk efficiently (without use of crutch or walker) and have to use especial prosthesis [2, 4]. Various types of components have been designed for hip disarticulation and hip pelvectomy to enable the subject to stand and walk [4, 5]; however, they have several problems including high energy consumption during walking, slow walking speed, style of walking which is not cosmetically appealing, and limitation in range of motion of leg joints [610]. As a result of small number of prosthetics users there is limited number of research on this topic.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of small number of prosthetics users there is limited number of research on this topic. Furthermore, there are a few studies on kinetic and kinematic parameters of Canadian prosthesis users [6, 7, 9]. In one research study the loads applied on prosthesis were evaluated during walking of a subject with hip disarticulation amputation [8].…”
Section: Introductionmentioning
confidence: 99%